2016
DOI: 10.1007/s00392-016-0985-x
|View full text |Cite
|
Sign up to set email alerts
|

Prompt benefit of early immunosuppressive therapy in acute lymphocytic myocarditis with persistent heart failure

Abstract: Sirs:Myocarditis resolves in about 50 % of cases during 2-4 weeks, but 25 % develop persistent cardiac dysfunction and 12-25 % may deteriorate leading to death or endstage dilated cardiomyopathy [1]. Presentation with heart failure and ventricular dysfunction are strong predictors of adverse outcome [2]. Viral infection is the most commonly identified cause of myocarditis. Mechanisms of injury include direct viral damage or inappropriate immune response. While the initial immune response limits the degree of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Our approach was successful in this rare case and although no infectious, immune-mediated, or toxic reason was detectable here, biopsy confirmed our treatment strategy and ensured not to have missed any specifically treatable cause. This is in accordance with current literature [110]. …”
Section: Discussionsupporting
confidence: 94%
“…Our approach was successful in this rare case and although no infectious, immune-mediated, or toxic reason was detectable here, biopsy confirmed our treatment strategy and ensured not to have missed any specifically treatable cause. This is in accordance with current literature [110]. …”
Section: Discussionsupporting
confidence: 94%
“…Reiff and Missov recently reported a case of fulminant lymphocytic myocarditis successfully treated with immunosuppressive therapy [ 6 ]. Weitsman et al also reported on the effectiveness of early immunosuppressive therapy in acute lymphocytic myocarditis with persistent heart failure [ 7 ]. In these previous reports, the presence of virus and its association with clinical outcomes were mainly discussed, whereas the presence of eosinophil degranulation was not described.…”
Section: Discussionmentioning
confidence: 99%